Internalization of Positive Language in Religious Coping to Enhance Madrasah Students’ Academic Self-Efficacy - Khusniyah, Aziizatul; Rahmajati, Erina; Aditya Widyansyah, Jonathan; Fanny Nafiza Imaniyyah, Siti (Majalah Ilmiah UPI YPTK, 2025)
This community service program aims to enhance the academic self-efficacy of Madrasah students through the internalization of positive language as a form of religious coping. The program was developed based on previous research findings indicating that religious coping through positive self-talk contributes significantly to the improvement of adolescents’ self-efficacy. Preliminary observations conducted at MA Darussa’adah revealed that many final-year students experienced low academic confidence, particularly in relation to pursuing higher education, due to perceived limited opportunities and socio-economic constraints.Using a community-based participatory approach, this program implemented a series of guided activities focusing on positive self-talk integrated with muhasabah (self-reflective religious practice). Language was positioned as an internal cognitive and affective tool that helps students regulate emotions, reconstruct self-perception, and strengthen belief in their academic abilities. The activities included reflective discussions, affirmation exercises, and guided muhasabah sessions designed to internalize positive and faith-based language patterns.The results of the program indicate an observable improvement in students’ academic self-efficacy, reflected in increased confidence, more positive self-statements, and stronger motivation to pursue higher education. This community service initiative demonstrates that the internalization of positive language within a religious coping framework can serve as an effective strategy to empower Madrasah students academically and psychologically. The program also highlights the potential integration of linguistic, educational, and religious approaches in community-based interventions for adolescent development.